Resolution of child custody dispute: legislative foundation and contemporary application of sulh in the shariah court of Malaysia (Mediasi dalam menyelesaikan isu penjagaan kanak-kanak: asas perundangan dan aplikasi sulh oleh mahkamah syariah di Malaysia ) - Abdul Hak, Nora; Mansor, Ahmad Mukhlis; Che Soh @ Yusoff, Roslina (International Islamic University Malaysia (IIUM), 2020)
Mediation or sulh at the Malaysian Shariah Court deals with a variety of issues relating to Islamic family law including the child custody issues. Disputes that exist between the parties can be resolved through litigation (court) and non-litigation (outside the court). Sulh is one of the non-litigation methods in settling disputes in peace and harmony. The Government initiative by introducing sulh since 2001 helps in reducing the backlog of cases, speeds up settlement of dispute and it has become a very constructive method of resolving disputes amicably. This article aims to discuss and analyse the principles of sulh in Islamic Law, its foundations and its implementation in Malaysia particularly in child custody disputes. The article also will look at how sulh interacts with the new implementation of the Special Court of Hadanah established in the Shariah Court of Federal Territories (MSWP). The methodology adopted, is library-based research to collect information, data and theories involved, from selected materials including journal articles, textbooks, statutes, as well as interview method. The data were analysed using the content analysis method. The study concludes that the practice of sulh in the child custody disputes is not only in line with the Islamic Law but also plays a vital role in protecting the children‖s rights as outlined by the intent of the Divine Guidance (Maqasid Shariah).